Inactivation Kinetics of G‐Quadruplex/Hemin Complex and Optimization for More Reliable Catalysis. Issue 7 (11th May 2022) - Monte Carlo, Anthony R.; Fu, Jinglin
Abstract: Reliable catalysis is critical for the synthesis of various chemicals, molecular sensing and biomedicine. G‐quadruplex/Hemin (GQH) complex, a peroxidase‐mimicking DNAzyme, has been widely used in various publications. However, a concern exists about the unstable kinetics of GQH‐catalyzed peroxidation. This work investigates several factors that result in the inactivation of GQH and the signal degradation during long reaction periods, including pH, buffer component, the selection of substrate and the oxidation damage of cofactor. Using colorimetric and fluorescent assays, GQH was found to be highly unstable under basic conditions with 50 % of GQH activity lost within 2 minutes at high H2 O2 concentrations. Appropriate conditions and substrates are suggested for accurately characterizing GQH‐catalyzed reactions, as well as optimization to improve the catalytic reliability, such as the use of polyhistidine and cascade reactions. These results could be useful for GQH‐related applications. Abstract : The catalytic instability of G‐quadruplex/hemin (GQH) was investigated for several factors, including buffer conditions, the selection of substrate and the oxidation damage. The reliability of GQH‐catalyzed reaction was improved by using appropriate conditions and the addition of "adjuvant". The study provides useful information to benefit GQH‐related applications.